BUILDING STUDENT CHARACTER THROUGH LEARNING MATHEMATICS - Vina Amilia Suganda; Siti Hawa; Sulkipani Sulkipani (Sriwijaya University Learning and Education International Conference, 2018)
This literature study aims to analyze the learning of mathematics to build the character of students in elementary school. Mathematical learning has a close relationship with everyday life. Thus mathematics will relate to the character of students such as honesty, social care and discipline. The concept of honesty in mathematics learning is depicted in social arithmetic material that introduces about profits, and losses. The character of discipline in mathematics can be interpreted in material such as debit. Attempts to build student character in learning are also the responsibility of the teacher. Thus prospective teachers must have superior competence in order to build the character of students through learning mathematics. Positive characters built through the learning of mathematics since the elementary school, is expected to be a habituation to students as a provision for life.